2015
DOI: 10.1186/s12961-015-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for sustainability of Academic Collaborative Centres for Public Health in the Netherlands: a mixed methods design

Abstract: BackgroundContemporary research should increasingly be carried out in the context of application. Nowotny called this new form of knowledge production Mode-2. In line with Mode-2 knowledge production, the Dutch government in 2006 initiated the so-called Academic Collaborative Centres (ACC) for Public Health. The aim of these ACCs is to build a regional, sustainable knowledge-sharing network to deliver socially robust knowledge. The present study aims to highlight the enabling and constraining push and pull fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In some jurisdictions, researcher and research user partnerships have become routinised in the structures and processes relied upon to generate and implement research. The Netherlands invested over 30 million euros to establish 11 Academic Collaborative Centres between 2006 and 2014, which involved partnerships between healthcare organisations and universities, leading to 150 short-and long-term policy-driven projects to improve public health [6]. Similarly, in England, 200 million pounds were invested to create 9 Collaborations for Leadership in Applied Health Research and Care (CLARHCs) between 2008 and 2013, which are regional partnerships between healthcare organisations and universities that improved healthcare delivery (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In some jurisdictions, researcher and research user partnerships have become routinised in the structures and processes relied upon to generate and implement research. The Netherlands invested over 30 million euros to establish 11 Academic Collaborative Centres between 2006 and 2014, which involved partnerships between healthcare organisations and universities, leading to 150 short-and long-term policy-driven projects to improve public health [6]. Similarly, in England, 200 million pounds were invested to create 9 Collaborations for Leadership in Applied Health Research and Care (CLARHCs) between 2008 and 2013, which are regional partnerships between healthcare organisations and universities that improved healthcare delivery (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it is now well-recognized that partnerships between researchers and research users who co-generate knowledge, a process often referred to as integrated knowledge translation (IKT), are an effective means of enabling the uptake of research evidence to optimize healthcare planning, delivery, and outcomes [24]. IKT can empower research users that were traditionally passive consumers of knowledge to have a say in its creation or direction [5, 6], create capacity to make research evidence context-sensitive to local health care needs [7], and prime knowledge users, who may be involved in various steps of the research process, to apply that knowledge [8]. Research users include clinicians, managers, patients, family members or caregivers, health system leaders or policy-makers, and other stakeholders who may use the research [9].…”
Section: Introductionmentioning
confidence: 99%
“…Large scale examples include the Collaborations for Leadership in Applied Health Research and Care (CLAHRCs) in the United Kingdom (UK) [11] or the Academic Collaborative Centres (ACCs) in the Netherlands [12]. In both cases, considerable resources were invested at a national level in establishing the capacity to support partnerships between researchers and research users, leading to increased IKT activity, and use of evidence to inform policy and practice [7, 11]. Research based on these and other partnerships revealed numerous factors influence IKT and its impact; they include establishing a physical space for communication and collaboration, preferably at close geographical proximity [2, 13], setting roles, goals and responsibilities for team members [2, 1416], setting leadership for projects [2, 7], and funding for grants and incentives [7, 16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An available intervention is at best a hopeful design, and realising it locally in practice requires work by many actors and heterogeneous learning processes. Awareness that most of the work and learning required for realising an effective intervention has to happen locally is essential [ 24 ]. The fourth component of the lure of effectiveness is that an illusion can emerge that quality can be centrally assured.…”
Section: Discussionmentioning
confidence: 99%